Impact of Intraoperative Blood Transfusions on Survival Rates in Ovarian Cancer Patients - Steven Benyahia BA; Monica Avila MD; Emily Coughlin MPH; Amreesh Mahil MD; Alejandra Riveron MD; Yi Luo PhD; Robert Wenham MD; Jeffrey Huang MD (Cancer Control)
Introduction Ovarian cancer remains a leading cause of gynecologic cancer-related mortality worldwide. Identifying perioperative factors that influence survival outcomes is essential for optimizing care. This study evaluates the impact of perioperative factors such as intraoperative blood transfusions and hospital length of stay (LOS) on survival rates in ovarian cancer patients undergoing surgical debulking. Methods This retrospective study analyzed charts of 314 patients who underwent ovarian cancer surgery at a single institution between 2010 and 2018. Patients were grouped based on survival status: “Live” or “Death”. Variables included demographics, tumor size, comorbidity, anesthesia time, surgery time, estimated blood loss, transfusion, readmission, hospital stay length, and survival. Statistical analyses included log-rank tests and mean survival estimations: chi-square tests and Mann-Whitney U-test. Significance was set at P < .05. Results The mean follow-up was 50.5 months (95% CI, 47.8-53.2). Prolonged LOS (>3 days) was significantly associated with reduced survival (47.4 vs 52.4 months, P = .015). Patients requiring intraoperative blood transfusions had poorer survival outcomes (42.0 months 95% CI, 36.3-47.7 vs 53.1 months 95% CI, 50.3-55.9, P < .001). The “Death” group experienced greater blood loss, longer surgical/anesthesia times, and higher intraoperative fluid requirements. Conclusion Prolonged hospital stays and intraoperative blood transfusions are associated with worse survival outcomes in ovarian cancer patients undergoing surgery. These findings underscore the importance of perioperative optimization strategies, including minimizing transfusion requirements and reducing LOS through enhanced recovery protocols.